Implementation of the Educational Management Information System (Emis) in the Annual Compilation Program - Arhami, Arhami; Mustaring, Dodi Ilham; Arifuddin, Arifuddin (Global Education Journal, 2025)
The rapid development of information and communication technology has had a profound impact on the education sector, especially in the management of data and information systems. The aim of this research is to analyze the Implementation of the Educational Management Information System (Emis) in the Annual Compilation Program at Palopo State Islamic Junior High School. Qualitative method. Data collection using interviews and observations. The implementation of EMIS at MTsN Palopo plays a vital role in managing accurate data for annual program planning, covering student information, class groupings, resources, and funding. Its policy involves organization, interpretation, and application stages with collaboration among staff, regular training, and support from the Ministry of Religious Affairs. Despite its importance as a tool for monitoring and evaluation, challenges such as incomplete or inconsistent student data, unreported transfers, and technical constraints from the central system remain obstacles to its optimal use.